A Central Role for Long Non-Coding RNA in Cancer - Mitra, Sheetal A.; Mitra, Anirban P.; Triche, Timothy J. (Frontiers in Genetics, 2012)
Long non-coding RNAs have been shown to regulate important biological processes that support normal cellular functions. Aberrant regulation of these essential functions can promote tumor development. In this review, we underscore the importance of the regulatory role played by this distinct class of non-coding RNAs in cancer-associated pathways that govern mechanisms such as cell growth, invasion and metastasis. We also highlight the possibility of using these unique RNAs as diagnostic and prognostic biomarkers in malignancies.